Relationships Between Advanced Cancer Patients' Worry About Dying and Illness Understanding, Treatment Preferences, and Advance Care Planning - Rodenbach, Rachel A.; Althouse, Andrew D.; Schenker, Yael; Smith, Thomas J.; Chu, Edward; White, Douglas B.; Bakitas, Marie; Arnold, Robert M. (Journal of pain and symptom management, 2021)
Patients with advanced cancer often worry about dying. Less is known about the role of worry in decision making regarding future care. To explore relationships between patients' worry about dying and their illness understanding, treatment preferences, and advance care planning (ACP). This cross-sectional study used baseline data from a primary palliative care intervention trial. All participants had metastatic solid tumors. Using patients' response to I worry about dying from the Functional Assessment of Chronic Illness—Palliative Care survey instrument, univariate and multivariate analyses assessed associations with illness understanding, treatment preferences, and ACP. Of 672 patients, 47% reported worrying about dying not at all, whereas 9.7% worried quite a bit or very much. In regression analysis, compared with patients who reported not worrying about dying, those who reported high levels of worry were more likely to describe themselves as terminally ill (adjusted odds ratio [AOR] = 1.98; 95% CI = 1.10–3.54; P = 0.021) and prefer life-extending therapy over symptom-focused care (AOR = 2.61; 95% CI = 1.30–5.22; P = 0.007). They were less likely to have completed an advance directive (AOR = 0.49; 95% CI = 0.25–0.94; P = 0.032). The same relationships were seen using patients' response to I feel scared about my future from the Herth Hope Index. Patients with advanced cancer who worry about dying are more likely to identify as terminally ill and desire life-extending treatment and are less likely to engage in ACP. Understanding how patients cope with worry and make medical decisions is important in providing quality care to these patients.